Realismo moral: proposta a partir da teoria popperiana dos Três Mundos - Romanini, Mateus (2016)
This work is primarily engaged in formulating a moral realism proposition based on Karl Popper s Three Worlds Theory. As there is a range of metaethical positions in question, first we seek to present the contemporary meta-ethical debate in order to place some of the key positions existing in it and explain why we assume moral realism. After this presentation, we approach in more detailed way what constitutes moral realism, presenting some of its main aspects as well some of the best-known criticisms that are made to this position. In a third step, already developing the proposal of moral realism that we fetch to formulate in this paper, we explain the Theory of Three Popper Worlds, a theory which states that the reality of the way that humans know consists of the interaction of three worlds: physical world (world 1), the world of mental states (world 2) and the objective world of abstract entities (world 3). From these three worlds, that most important for us is the world 3 because it is inhabited by different types of objective abstract entities, among which we suggest here, is the idea of good and the moral facts, so we call our proposed World 3 Moral Realism. The idea of good is that we consider to be the idea that governs the search for solutions to moral problems, these solutions once established through continuous use of language, especially of the higher functions that characterize human language, become objective moral facts which, in turn, are the references to the truth of moral discourse and the correction of moral actions. Finally, we seek to show how our proposal fulfills the necessary conditions for it to be considered a moral realism and also point out some negative aspects and some positive aspects since we can already identify in this kind of realism. After weigh these aspects, we maintain that this is a promising proposal and therefore deserves a place in the list of metaethical positions.